Rationalizing myths base of authority dystopia, in the neoliberal governments of Macri - Argentina and Piñera - Chile - REZA GRANADOS, Rebeca; ASCENCIO LÓPEZ, Noemí (Utopía y Praxis Latinoamericana, 2025)
The objective of this document is to address the analysis of neoliberal dystopias, through the rationalization myths and their institutionalization process, the development and implementation of migration policies, their interaction with the governments of the right, Macri from Argentina and de government, second, Piñera from the Chile – whit migrant citizen ship -from Peru-. This investigation, use the ethnomethodology, the building narratives; the case’s study, and, thus, we can see how the paradox of the free market and the rational choice -homus economicus- are transformed into neoliberal dystopias, chose empiricism is manifested through establishing, in an operational way -legitimized or not- omnipresent States, whose governments base their political work, denying migrants their human rights, starting with dignity.